Role of Psychological Factors in Individuals Investment Decisions - Lubis, Hasrita; Kumar, M. Dileep; Ikbar, P.; Muneer, Saqib (International Journal of Economics and Financial Issues, 2015)
In this study, the authors intend to identify psychological factors which could influence the criteria for investment decision which are discussed with three dimensions (risk, repay and corporate data). With regard to this aim, the criteria for investment decision were examined through defense mechanisms, personality traits, emotional intelligence and financial literacy. Defense mechanisms and certain personality traits have become prominent for risk criterion while defense mechanisms and financial literacyhave been important to repay criterion. Lastly, for corporate data criterion, defense mechanisms, some personality traits and emotional intelligence have been found as important. Within this scope, this study can be said to have carried out a preliminary research in its field in terms of explanatory variables. Keywords: Investment Decision, Defense Mechanisms, Personality Traits, Emotional İntelligence, Financial Literacy JEL Classifications: E44, G23